Music-based Intervention for Improving Sleep Quality of Adults without Sleep Disorder: A Systematic Review and Meta-analysis. Issue 2 (4th March 2022) - Tang, Yee Woon; Teoh, Siew Li; Yeo, Julie Hsiao Hui; Ngim, Chin Fang; Lai, Nai Ming; Durrant, Simon James; Lee, Shaun Wen Huey
ABSTRACT: Background: Listening to music is often used as a self-help intervention to improve sleep quality, but its efficacy among individuals without sleep disorder remains unclear. Methods: A search was performed on five databases to identify for studies that examined the use of music-based intervention to improve sleep quality among individuals without sleep disorder. Random-effects meta-analysis was performed, and the certainty of evidence was evaluated using GRADE (Grading of Recommendations Assessment, Development and Evaluation). Results: Twenty-two articles which recruited 1, 514 participants were included for review. Meta-analysis of six studies including 424 participants did not find an improvement in sleep quality among recipients of music-based intervention compared to those with standard care (mean difference: −0.80; 95% CI: −2.15 to 0.54, low-quality evidence). Subgroup analysis showed a clear improvement in sleep quality when interventions were administered for at least 3 weeks (−2.09; −3.84 to −0.34, n = 3). No difference in terms of sleep onset latency (standardized mean difference (SMD) −0.32; 95% CI −0.88 to 0.25, n = 4, very-low quality evidence) and sleep efficiency (SMD: −0.59; 95% CI −3.15 to 1.97, n = 2, very-low quality evidence) were observed. The effect of music-based intervention on anxiety, depression and quality of life were mixed with suggestions of possible benefits. Conclusion: Music-based intervention in addition to standard care appears to be a promising strategy to improve sleep quality when delivered for 3 week or longer. However, effects are inconsistent across studies and larger randomized controlled studies reporting long-term outcomes are needed before it can be recommended for routine use. PROSPERO registration: CRD42018081193